EDUCATION MANAGEMENT EFFECTIVENESS AT STATE SENIOR HIGH SCHOOL FOR ISLAMIC STUDIES 2 MANDAILING NATAL - Fatkhur Rohman; Yani Lubis; Martha Beck (The Islamic Education and Multiculturalism Foundation, 2022)
Abstract. This study aims to determine the Education Personnel Management Effectiveness ofat State Senior High School For Islamic Studies (MAN) 2 Mandailing Natal, namely: 1) employee planning, 2) employee procurement, 3) coaching and staffing, 4) promotion and transfer, 5) employee termination, 6) compensation, and 7) employee evaluation and development management of Education Personnel at MAN 2 Mandailing Natal. The approach used in this research is a qualitative approach. The place that became the object of this research was Madrasah Aliyah Negeri (MAN) 2 Mandailing Natal, which is located on Jl. Teuku Umar Pasar III Natal, Natal District. The results of the study show that: The required staff planning is adjusted to the required students. Therefore, before preparing a plan, it is necessary to carry out a job analysis and job analysis to obtain a job description (an overview of the tasks and work to be carried out). Procurement of employee educators always conforms to the plan that has been prepared by the Head of Madrasah and staff at the madrasah for procuring staff themselves must go through a recruitment process, oral exams, written exams, and practical exams, so far the procurement of teaching staff has only used exams writing and studying. The development of employee education staff at MAN 2 Mandailing Natal must always be specifically related to the development and career paths of teaching staff according to the category of each type of teaching staff themselves. Promotion, transfer, dismissal, compensation and evaluation of employees always refer to the rules that are in accordance with the provisions.